2015
DOI: 10.1016/j.athoracsur.2014.08.051
|View full text |Cite
|
Sign up to set email alerts
|

Lung Cancer With Tumor Emboli

Abstract: We report a case of squamous cell lung carcinoma that invaded the left atrium through the left pulmonary vein. This patient had two episodes of systemic embolism before diagnosis. The second episode was treated with embolectomy, and the pathology analysis showed squamous cell carcinoma. The tumor was surgically resected, using cardiopulmonary bypass to resect the intracardiac portion. We discuss causes of tumor emboli in lung cancer and surgical treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 7 publications
(13 reference statements)
0
5
0
Order By: Relevance
“…Nearly all reports of systemic arterial embolization in patients with any primary malignancy have discussed the mechanism by which pulmonary metastases, pulmonary primary tumors, or cardiac malignancies invade the pulmonary veins (PVs), fragment within the left atrium or within the PVs and subsequently enter the systemic circulation. 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 Another recognized mechanism is when the heart or aorta has been directly invaded by the tumor owing to proximity, achieving direct access to the arterial circulatory system. 4 , 5 , 6 , 7 , 8 , 9 Finally, in patients with known invasive lung cancer undergoing surgery, it has been reported that surgical manipulation of the PVs can result in arterial embolization.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Nearly all reports of systemic arterial embolization in patients with any primary malignancy have discussed the mechanism by which pulmonary metastases, pulmonary primary tumors, or cardiac malignancies invade the pulmonary veins (PVs), fragment within the left atrium or within the PVs and subsequently enter the systemic circulation. 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 Another recognized mechanism is when the heart or aorta has been directly invaded by the tumor owing to proximity, achieving direct access to the arterial circulatory system. 4 , 5 , 6 , 7 , 8 , 9 Finally, in patients with known invasive lung cancer undergoing surgery, it has been reported that surgical manipulation of the PVs can result in arterial embolization.…”
Section: Discussionmentioning
confidence: 99%
“… 4 , 5 , 6 , 7 , 8 , 9 Finally, in patients with known invasive lung cancer undergoing surgery, it has been reported that surgical manipulation of the PVs can result in arterial embolization. 7 , 8 , 9 …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations